Boundary layer flow past a continuously moving thin needle in a nanofluid. (5th March 2017) - Soid, Siti Khuzaimah; Ishak, Anuar; Pop, Ioan
Highlights: We simulate the fluid flow over a thin needle immersed in a nanofluid. The solutions were obtained numerically using bvp4c in Matlab software. Two (dual) solutions are possible for a certain range of parameter. A stability analysis is performed to determine which solution is linearly stable. The solution domains are smaller in the existence of the nanoparticles. Abstract: A steady two-dimensional laminar forced convection boundary layer flow along a horizontal thin needle immersed in a nanofluid is considered. The governing partial differential equations are first reduced to a system of nonlinear ordinary differential equations, before being solved numerically using the boundary value problem solver (bvp4c) in Matlab, for copper-water nanofluid with Prandtl number Pr = 6.2 (water). The physical quantities of interest such as the skin friction coefficient and the local Nusselt number as well as the velocity and temperature profiles are presented. Dual solutions are found when the needle and the free stream move in the opposite directions. It is seen that the solution domain decreases with increasing values of the solid volume fraction parameter. The influences of the needle size and the solid volume fraction parameter on the flow and heat transfer characteristics as well as on the velocity and temperature profiles are investigated.